Autoimmunity (or Not) in Atopic Dermatitis - Roesner, Lennart M.; Werfel, Thomas (Frontiers in Immunology, 2019)
Atopic dermatitis (AD), one of the most frequent inflammatory skin diseases worldwide, is believed to result from a disturbed skin barrier as well as aberrant immune reactions against per se harmless allergens. Starting mostly during childhood with a chronic, remitting relapsing course, the disease can persist into adulthood in about one fifth of patients. Immune reactions to self-proteins have been observed in AD patients already in the beginning of the 20th century, when human cellular extracts were shown to provoke skin lesions. However, the term “autoimmunity” has never been claimed, since AD is first and foremost an atopic disease. In contrast, this IgE-hallmarked autoreactivity was termed “autoallergy” and is ongoing discussed regarding its impact on the disease. Since severely affected patients tend to develop IgE-hypersensitivity reactions to numerous environmental allergens, the impact of immune responses to self-proteins is difficult to determine. On the other hand: any autoreactivity, irrespective of the magnitude, implicates the potential of driving the chronification of the disease while shaping the immune response. This review article revisits the observations made on autoallergy from an actual point of view and tries to approach the question whether these still point to a contribution to the disease.